Immune checkpoint inhibitors in epidermal growth factor receptor mutant non-small cell lung cancer: Current controversies and future directions. (January 2018) - Soo, Ross A.; Lim, Sun Min; Syn, Nicholas L.; Teng, Rebecca; Soong, Richie; Mok, Tony S.K.; Cho, Byoung Chul
Highlights: EGFR mutant NSCLC are more likely to have decreased PD-L1 expression. Uninflamed tumor microenvironment may explain poor response to checkpoint inhibition. Predictive biomarkers to PD-1/PD-L1 inhibitors sensitivity in EGFR  + NSCLC are needed. EGFR TKI and immune checkpoint inhibitors are being investigated extensively. Abstract: Major advances with the development of epidermal growth factor receptor tyrosine kinase inhibitors and immune check-point inhibitors have ushered in a new era in lung cancer therapy. Whilst pre-clinical studies suggest EGFR-driven NSCLC inhibit antitumor immunity through the activation of the PD-1/PD-L1 pathway, epidemiology studies suggest EGFR mutant NSCLC are more likely to have decreased PD-L1 expression. The superiority of single agent PD-1/PD-L1 inhibitors over docetaxel in pre-treated EGFR mutant NSCLC appears to be moderated. Several mechanisms for a poor response to immune checkpoint have been proposed including a lower tumor mutation burden, and an uninflamed and immunosuppressive tumor microenvironment. Predictive biomarkers to PD-1/PD-L1 inhibitors sensitivity in patients with EGFR mutations are required. The role of EGFR TKI in combination with an immune checkpoint inhibitor is currently being investigated intensively in multiple clinical trials and outcomes from these trials are immature and the optimal sequence, schedule and dosing remains to be determined. A careful evaluation will be required in view of the increased toxicities reported in some of the early studies of combination therapy.